2015
DOI: 10.1002/cssc.201500700
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐Assisted Ball Milling of Cellulose as an Efficient Pretreatment Process for the Production of Butyl Glycosides

Abstract: Ball milling of cellulose in the presence of a catalytic amount of H2SO4 was found to be a promising pre-treatment process to produce butyl glycosides in high yields. Conversely to the case of water, n-butanol has only a slight effect on the recrystallization of ball-milled cellulose. As a result, thorough depolymerization of cellulose prior the glycosylation step is no longer required, which is a pivotal aspect with respect to energy consumption. This process was successfully transposed to wheat straw from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…ChemSusChem 2018ChemSusChem , 11,1395ChemSusChem -1409 www.chemsuschem.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim which can be further processedt od ownstream chemicals such as glucose, 5-hydroxymethylfurfural,o rh exitols. [23] Cellulose was first impregnated with 10 wt %o f H 2 SO 4 and was then ball-milled for 1h.N ext, the recovered acidulated glucans were suspended in 30 equivalents of n-butanol and heateda tr eflux for 3h(Scheme 5). [23] Cellulose was first impregnated with 10 wt %o f H 2 SO 4 and was then ball-milled for 1h.N ext, the recovered acidulated glucans were suspended in 30 equivalents of n-butanol and heateda tr eflux for 3h(Scheme 5).…”
Section: Direct Transglycosylation Of Cellulose With Fatty Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChemSusChem 2018ChemSusChem , 11,1395ChemSusChem -1409 www.chemsuschem.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim which can be further processedt od ownstream chemicals such as glucose, 5-hydroxymethylfurfural,o rh exitols. [23] Cellulose was first impregnated with 10 wt %o f H 2 SO 4 and was then ball-milled for 1h.N ext, the recovered acidulated glucans were suspended in 30 equivalents of n-butanol and heateda tr eflux for 3h(Scheme 5). [23] Cellulose was first impregnated with 10 wt %o f H 2 SO 4 and was then ball-milled for 1h.N ext, the recovered acidulated glucans were suspended in 30 equivalents of n-butanol and heateda tr eflux for 3h(Scheme 5).…”
Section: Direct Transglycosylation Of Cellulose With Fatty Alcoholsmentioning
confidence: 99%
“…[22] Inspired by this work, JØrôme and co-workers recently reported the direct transglycosylation of cellulosew ith n-butanol in at wo-step process. [23] Hence,e xtensive depolymerization of cellulose during the mechanocatalytic step is not mandatory before the glycosylation reaction. Undert hese conditions, n-butyl-a/b-d-glucosides were produced in 62 % yield.…”
Section: Direct Transglycosylation Of Cellulose With Fatty Alcoholsmentioning
confidence: 99%
“…Boissou et al. (Scheme ) reported that the mechanocatalytic treatment of acid‐impregnated cellulose was more advantageous for glycosylation (alcoholysis) than hydrolysis . After H 2 SO 4 ‐assisted ball milling, the yield of glucose in cellulose hydrolysis was only 11 %, whereas that of butyl glycosides reached 56 % in butanol at 117 °C for 5 h. Kinetic data suggested that the glycosylation rate of acid‐assisted ball‐milled cellulose was seven times faster than that of hydrolysis.…”
Section: Alcoholysis Of Lignocellulosementioning
confidence: 99%
“…Boissou et al (Scheme 2) reported that the mechanocatalytic treatment of acid-impregnated cellulose was more advantageous for glycosylation( alcoholysis) than hydrolysis. [18] After H 2 SO 4 -assisted ball milling,t he yield of glucosei nc ellulose hydrolysis was only 11 %, whereas that of butyl glycosides reached5 6% in butanol at 117 8Cf or 5h.K inetic data suggested that the glycosylationr ate of acid-assisted ball-milled cellulose was seven times faster than that of hydrolysis.T he water mediuml eads to the recrystallization of ball-milled cellulose to ah igher degree of structural order,w hereas it is obviously inhibited in n-butanol. More critically,t his acid-assisted ball-mill-ing method can be adopted to convert raw wheat straw, at ype of lignocellulose feed.…”
Section: Alcoholysis Of Cellulose To Alkyl Glucosidesmentioning
confidence: 99%
“…As the necessity of environmentally benign processes has grown, attention has focusedo ne asily separables olid catalysts for converting cellulose, [6,8,12,13] such as ion-exchange resins, [14] sulfonated carbon materials, [15,16] sulfonatedc arbon-silica nanocomposites, [17] weakly acidic amorphous carbons, [18,19] az eolite-templated carbon, [20] graphene oxide, [21] metal oxides, [22] and supported metal catalysts. [15,17,[24][25][26][27] Although amorphous cellulose can be more easily decomposed into oligosaccharides compared to crystalline cellulose, [28,29] the poor affinity between cellulose and mostc atalysts needs to be overcome. [15,17,[24][25][26][27] Although amorphous cellulose can be more easily decomposed into oligosaccharides compared to crystalline cellulose, [28,29] the poor affinity between cellulose and mostc atalysts needs to be overcome.…”
Section: Introductionmentioning
confidence: 99%